Inflammatory miofibroblastic tumor of the biliary tract in a pediatric patient - Prado-Cucho, Sofía (2020)
The inflammatory myofibroblastic tumor is an infrequent mesenchymal neoplasm, making the clinical as well as the pathological diagnosis by biopsies is a challenge. We present a case of a pediatric patient with an inflammatory myofibroblastic tumor located at the level of the bile ducts. We sent the lesion sample for intraoperative analysis through freezing techniques, the microscopic report was also incorrect. However, when the plates were reviewed after the inclusion of the lesion and supplemented byimmunohistochemical studies, it was concluded that the lesion corresponded to an inflammatory myofibroblastic tumor.